2014
DOI: 10.1371/journal.pone.0099396
|View full text |Cite
|
Sign up to set email alerts
|

Fucoidan Can Function as an Adjuvant In Vivo to Enhance Dendritic Cell Maturation and Function and Promote Antigen-Specific T Cell Immune Responses

Abstract: Fucoidan, a sulfated polysaccharide purified from brown algae, has a variety of immune-modulation effects, including promoting antigen uptake and enhancing anti-viral and anti-tumor effects. However, the effect of fucoidan in vivo, especially its adjuvant effect on in vivo anti-tumor immune responses, was not fully investigated. In this study, we investigated the effect of fucoidan on the function of spleen dendritic cells (DCs) and its adjuvant effect in vivo. Systemic administration of fucoidan induced up-re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
110
1
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 124 publications
(122 citation statements)
references
References 34 publications
6
110
1
1
Order By: Relevance
“…Notably, configurations where either IL-15:IL-15R␣ or OVA was detached from the NPs did not enhance animal sur- vival beyond the control group. Our findings align with recent literature showing that OVA vaccination requires an adjuvant to potentiate antigen-specific protective immunity (97)(98)(99)(100) and further highlight the importance of adjuvant configuration in the case of IL-15. Overall, we show that nanoparticles transpresenting IL-15:IL-15R␣ and encapsulating antigen demonstrate in vivo efficacy in the treatment of an aggressive model of murine melanoma.…”
Section: Il-15:il-15r␣ and Encapsulated Antigen Synergize To Delay Tusupporting
confidence: 91%
“…Notably, configurations where either IL-15:IL-15R␣ or OVA was detached from the NPs did not enhance animal sur- vival beyond the control group. Our findings align with recent literature showing that OVA vaccination requires an adjuvant to potentiate antigen-specific protective immunity (97)(98)(99)(100) and further highlight the importance of adjuvant configuration in the case of IL-15. Overall, we show that nanoparticles transpresenting IL-15:IL-15R␣ and encapsulating antigen demonstrate in vivo efficacy in the treatment of an aggressive model of murine melanoma.…”
Section: Il-15:il-15r␣ and Encapsulated Antigen Synergize To Delay Tusupporting
confidence: 91%
“…Various polysaccharides, including fucoidan, ascophyllan and λ-carrageenan, have shown immune activation and anti-cancer effects [3, 19, 23, 24]. In this study, we showed that pullulan, a polysaccharide purified from Aureobasidium pullulans , promoted the activation of BMDCs in vitro and of spleen DCs in vivo, and induced anti-cancer immune responses.…”
Section: Discussionmentioning
confidence: 66%
“…Different subsets of DCs have different abilities of Ag-presentation and T cell activation. In mouse, conventional DCs (cDC) have two subsets: CD8α + CD11c + and CD8α − CD11c + cDCs [3, 19, 20]. CD8α + CD11c + cDCs are specialized in the cross-presentation of endogenously synthesized Ags through MHC class I to CTL [20, 21], and CD8α − CD11c + cDCs have the selective ability to present extracellular Ags directly through MHC class II to CD4 T cells [22].…”
Section: Introductionmentioning
confidence: 99%
“…Fucoidan , , , , , (Kuznetsova et al, 2014;Cho et al, 2015). , , , (Jin et al, 2014). fucoidan , , (Ahmed et al, 2014).…”
Section: 서 론 (Idiopathic Pulmonary Fibrosis Ipf)unclassified